The number and phenotype of myocardial and adipose tissue CD68+ cells is associated with cardiovascular and metabolic disease in heart surgery patients - Pierzynová, Aneta; Šrámek, Jaromír; Cinkajzlová, Anna; Kratochvílová, Helena; Lindner, Jaroslav; Haluzík, Martin; Kučera, Tomáš (Nutrition, metabolism, and cardiovascular diseases, 2019)
CD68+ cells are a potent source of inflammatory cytokines in adipose tissue and myocardium. The development of low-grade inflammation in adipose tissue is implicated in the pathogenesis of obesity-associated disorders including type 2 diabetes mellitus (T2DM) and cardiovascular disease. The main aim of the study was to characterize and quantify myocardial and adipose tissue CD68+ cells and adipose tissue crown-like structures (CLS) in patients with obesity, coronary artery disease (CAD) and T2DM. Samples were obtained from the right atrium, epicardial (EAT) and subcutaneous adipose tissue (SAT) during elective heart surgery (non-obese, n = 34 patients; obese, n = 24 patients). Immunohistochemistry was used to visualize CD68+ cells. M1-polarized macrophages were visualized by immunohistochemical detection of CD11c. The proportion of CD68+ cells was higher in EAT than in SAT (43.4 ± 25.0 versus 32.5 ± 23.1 cells per 1 mm2; p = 0.015). Myocardial CD68+ cells were more abundant in obese patients (45.6 ± 24.5 versus 27.7 ± 14.8 cells per 1 mm2; p = 0.045). In SAT, CD68+ cells were more frequent in CAD patients (37.3 ± 23.0 versus 23.1 ± 20.9 cells per 1 mm2; p = 0.012). Patients having CLS in their SAT had higher average BMI (34.1 ± 6.4 versus 29.0 ± 4.5; p = 0.024). Regional-based increases in the frequency of CD68+ cells and changes of their phenotype in CLS were detected in obese patients and CAD patients. Therapeutic modulation of adipose tissue inflammation may represent a target for treatment of obesity. •More macrophages in subcutaneous fat of CAD patients compared to patients without CAD.•More macrophages in myocardium of obese patients compared to non – obese patients.•BMI correlates with the number of crown-like structures in subcutaneous fat.•Crown-like structures in adipose tissue contain pro-inflammatory macrophages.•Macrophages are more frequent in epicardial fat than in subcutaneous fat.